Evaluate the Cooling Performance of Transmit/Receive Module Cooling System in Active Electronically Scanned Array Radar - Jun Su Park (Electronics, 2021)
The active electronically scanned array (AESA) radar consists of many transmit/receive (T/R) modules and is used to track missiles approaching destroyers and fighters. The performance of the AESA radar depends on the T/R module temperature. The T/R module temperature should be maintained under 80 °C to guarantee the performance of the AESA radar. In order to match the design requirements of the cooling system of the AESA radar, it is necessary to evaluate the cooling performance according to various operation/installation environments. In this study, computational fluid analysis was performed by changing the number of T/R modules and the coolant mass flow rate to evaluate the cooling performance of the AESA radar coolant channel. The number of T/R modules was changed from 2 to 16, and the number of coolant inlet Re was changed from 277 to 11,116. As a result, it was confirmed that the temperature increased as the number of T/R modules increased. In addition, when the coolant status was laminar flow, it was confirmed that the cooling performance was significantly lowered. Therefore, the coolant status should be transient or turbulence to decrease the temperature of the T/R module. Additionally, the correlation between the arrangement of the T/R module and the cooling flow must be considered to cool the AESA radar.